The microstructure of the great export collapse in German manufacturing industries, 2008/2009 - Joachim Wagner (Institute for the Study of Labor (IZA), 2012)
This paper uses comprehensive high-quality panel data from official statistics for exporting enterprises to investigate the micro-structure of the recent export collapse in manufacturing industries in Germany during the crisis of 2008/2009. Almost all of the decline in exports was due to negative changes of exports in firms that continue to export (i.e. at the so-called intensive margin) while the decrease of exports due to export stoppers (at the so-called extensive margin) was tiny. It is shown that Idiosyncratic shocks to very large firms played a decisive role in shaping the export collapse.
urn:nbn:de:101:1-201206146692
Keywords: F14; E32; 330; exports; great trade collapse; granular economy; Germany; Export; Wirtschaftskrise; Schock; Exportindustrie; Industriegüteraußenhandel; Deutschland